Effects of cement kiln dust on physicochemical and geomechanical properties of loess soil, Semnan Province, Iran - O'Kelly, Brendan (My University, 2022)
For problematic soils, conventional (cement and lime) additives can provide the necessary improvements in geomechanical properties for various infrastructure constructions. However, these additives have a high environmental impact and they are not always cost-effective, such that potential alternative additives (e.g. obtained as industrial by-products) require investigation. This paper examines cement kiln dust (CKD), obtained as a by-product of cement clinker manufacturing, for improving the geomechanical properties of an Iranian loess soil (sandy silt). Compaction, unconfined compressive strength (UCS), direct shear (DS) strength and soaking durability tests were performed on the loess soil and its mixtures with 5–20% CKD, investigating the effect of curing period (of up to 28 days) on the mobilised strength. Observations from mineralogical and microstructural examinations are also presented in this paper. Compared to the unamended loess, the strength and elastic modulus substantially increased for increasing CKD content and curing period. Improved strength and durability (under soaking) of the soil–CKD mixtures is explained by particle aggregation (of the loess soil), inclusion of the fine CKD material and the action of calcium-derived gel (linking) products. Hence, as well as reducing the disposal problem (of the CKD by product) in the cement industry, the use of this material, as additive for soil stabilisation applications, would provide an effective and sustainable option for improving the geomechanical properties, as demonstrated for the investigated loess soil.
PUBLISHED
Free access to the full published article is provided via the following Share Link: https://rdcu.be/cUUH3
Keywords: Cement kiln dust; Loess; Microstructural characteristics; Soil improvement; Smart & Sustainable Planet; GEOTECHNICAL ENGINEERING; Geotechnics; SOIL MODIFICATION; Soil Mechanics; Soil Mechanics & Foundations; cement kiln dust; geotechnical; loess; loess soil; soil improvement; soil stabilization